A cross-sectional study of antibodies to ubiquitin proteasome system in different glomerulopathies - Chebotareva, Natalia; Cao, Venzsin; Vinogradov, Anatoliy; Alentov, Igor; Sergeeva, Natalia; Kononikhin, Alexey; Moiseev, Sergey (Clinical nephrology, 2023)
Recently, evidence has emerged that the ubiquitin system, which is involved in extracellular protein degradation, is most susceptible to damage in podocytes in cases of podocytopathies. We studied anti-ubiquitin carboxyl-terminal hydrolase L1 (UCHL1) antibodies in glomerulopathies with proteinuria. 71 patients with glomerulopathy and 11 healthy subjects were included in our study. 44 patients had nephrotic syndrome, and 27 did not. Serum levels of anti-UCHL1 antibodies were measured by ELISA. The levels of anti-UCHL1 antibodies were significantly higher in focal segmental glomerulosclerosis (FSGS) patients than in minimal change disease (MCD), IgA nephropathy, membranous nephropathy, or membranoproliferative glomerulonephritis patients and control group. The levels of UCHL1 antibodies in serum did not correlate with 24-hour proteinuria, blood pressure, glomerulosclerosis percentage, or area of tubulointerstitial fibrosis, but did correlate with serum creatinine and estimated glomerular filtration rate (eGFR). During the development of the ROC curve (AUC = 0.766 (95% CI 0.634 - 0.897)) for FSGS vs. other forms of glomerulopathies, a readjustment of the sensitivity of 75% and specificity of 61% were established. A former increase in anti-UCHL1 antibody levels above 1.93 ng/mL may be a marker of FSGS OR 3.617 (95% CI 1.051 - 12.447), p = 0.041. An increase in the level of anti-UCHL1 antibodies in the serum was noted in FSGS, which suggests that these antibodies could be a potential biomarker for FSGS patients.